Pengaruh Work Environment dan Characteristics Individu terhadap Kinerja Karyawan pada Perusahaan Daerah Air Minum (PDAM) Tirtalihou Kabupaten Simalungun - Marintan Saragih; Risma Nurhaini Munthe; Adat Muli Peranginangin (J-MAS (Jurnal Manajemen dan Sains), 2022)
The problem in this study is how the influence of the work environment and individual characteristics on employee performance at the Regional Water Company (PDAM) Tirtalihou Kabupaten Simalungun. Does the work environment and individual characteristics simultaneously affect the performance of employees at the Regional Water Company (PDAM) Tirtalihou Kab. Simalungun. This study aims to determine the effect of the work environment and individual characteristics on the performance of the employees of the Regional Water Company (PDAM) Tirtalihou Kab. Simalungun. This research is a research using a quantitative approach. The number of samples used were 36 respondents, because they were taken from 10% of the population of 360 people. The data analysis technique used in this research is multiple linear regression analysis. From the results of this study, the regression equation Y = 4.902 + 0.499 X1 + 0.357 X2 shows that the work environment (X1) has a positive effect on employee performance (Y), and individual characteristics (X2) have a positive effect on employees (Y). Partially there are work environment variables and individual characteristics that have a significant and positive effect on employee performance. Based on the results of the simultaneous test that the work environment variable (X1) and individual characteristics (X2) together have a positive and significant effect on employee performance.